Efeito de doses de fósforo e potássio na qualidade e produtividade de frutos de melancia na savana de Roraima - Oliveira, Edson Farias de (2011)
In the state of Roraima, watermelon is one of the most important crops exploited by both medium and small farmers. The objective of this study to test different doses of phosphorus and nitrogen in the culture of watermelon, and evaluate their effects on productivity and fruit quality. The experiment was carry out under field conditions in the randomized block design in the factorial scheme 4 x 4., constituted of four doses of phosphorus (60, 120, 180 and 240 kg ha-1 of P2O5) and four of doses potassium (60, 120, 180 and 240 kg ha-1 of K2O), respectively with three replications. The pH of fruit pulp, soluble solids content (ºBrix), the number of fruits per hectare, the average mass of fruits (kg), the commercial fruit yield (kg ha- 1) and percentage of fruits with mass < 6.0 kg, between 6.0 and 9.0 kg and >9.0 kg. The data were submitted to variance analysis with application of F test at 10% of probability and the means were submitted to polynomial regression analysis at 10% of probability. The classes of fruits were influenced by the doses of phosphorus and potassium, the pH of the fruits was influenced by the doses of potassium, the total soluble solids contents decreased with increasing doses of potassium up to 160 kg ha-1 of K2O, the number of fruits increased with the doses of K2O, the average mass of fruits was influenced by the doses of potassium, reaching the maximum value of 9.563 kg at the dose of maximum technical efficiency (162.5 kg ha-1 of K2O), the maximum fruit yield (56.757 kg ha-1) was obtained with the combination of the doses 120 and 173.16 kg ha-1 of P2O5 and of K20, respectively.